UPAYA MENINGKATKAN PEMAHAMAN KONSEP DASAR MATEMATIKA MATERI BANGUN RUANG PADA SISWA KELAS I SD MENGGUNAKAN MODEL REALISTIC MATHEMATIC EDUCATION (RME) - Salamah, Ema; Kelana, Jajang Bayu (COLLASE (Creative of Learning Students Elementary Education), 2020)
This research is a qualitative descriptive study that aims to determine the effectiveness of the application of the Realistic Mathematics Education model and the results of the evaluation of Realistic Mathematic Education in learning material building spaces in grade 1 students of SDIT Al-Fajar Bandung. The research method applied in this study uses a qualitative descriptive approach, namely research that provides an analysis of improving the understanding of mathematical concepts in building material with the existing procedures in applying the RME model, namely the preparation, opening, learning, and final stages. The evaluation of the RME model is seen from student activities based on aspects of oral activities and sees students who are enthusiastic and active in participating in learning activities, do not disturb friends while studying, dare to come to the front of the class and work on questions calmly and not in a hurry. The results showed that the application of the RME learning model on building materials could increase student learning activities and improve student learning outcomes. It can be seen from the results of the pretest students who achieved learning completeness by 27% then experienced an increase in the post-test results to 77%.